Protective efficacy of Toxoplasma gondii GRA12 or GRA7 recombinant proteins encapsulated in PLGA nanoparticles against acute Toxoplasma gondii infection in mice - Sun, Hong-chao; Deng, Pu-ming; Fu, Yuan; Deng, Jin-hua; Xie, Rong-hui; Huang, Jing; Qi, Meng; Shi, Tuan-yuan (Frontiers in Cellular and Infection Microbiology, 2023)
Background Toxoplasma gondii is an apicomplexan parasite that affects the health of humans and livestock, and an effective vaccine is urgently required. Nanoparticles can modulate and improve cellular and humoral immune responses. Methods In the current study, poly (D, L-lactic-co-glycolic acid) (PLGA) nanoparticles were used as a delivery system for the T. gondii dense granule antigens GRA12 and GRA7. BALB/c mice were injected with the vaccines and protective efficacy was evaluated. Results Mice immunized with PLGA+GRA12 exhibited significantly higher IgG, and a noticeable predominance of IgG2a over IgG1 was also observed. There was a 1.5-fold higher level of lymphocyte proliferation in PLGA+GRA12-injected mice compared to Alum+GRA12-immunized mice. Higher levels of IFN-g and IL-10 and a lower level of IL-4 were detected, indicating that Th1 and Th2 immune responses were induced but the predominant response was Th1. There were no significant differences between Alum+GRA7-immunized and PLGA+GRA7-immunized groups. Immunization with these four vaccines resulted in significantly reduced parasite loads, but they were lowest in PLGA+GRA12-immunized mice. The survival times of mice immunized with PLGA+GRA12 were also significantly longer than those of mice in the other vaccinated groups. Conclusion The current study indicated that T. gondii GRA12 recombinant protein encapsulated in PLGA nanoparticles is a promising vaccine against acute toxoplasmosis, but PLGA is almost useless for enhancing the immune response induced by T. gondii GRA7 recombinant protein.